Rapid Sequence Spinal Anesthesia Vs General Anesthesia for Category-I Urgency Caesarean Section - Gurvani, Dr. Ravi; Chandrakar, Dr. Dharam Veer (International Journal of Innovative Research in Medical Science, 2018)
Aims of study - Rapid Sequence spinal anesthesia Vs general anesthesia for category-I urgency caesarean section. Background - Pregnancy termination by caesarean section (CS) is rapidly increasing all over the world. Hence, it has increasingly become a greater challenge to provide care for the parturient, but this has given obstetric anesthetists a greater opportunity to contribute to obstetric services. While caesarean deliveries were historically performed using general anaesthesia, there is a recent significant move towards regional anaesthesia. Materials and Methods - As per American Society of Anesthesiologists physical status (ASAPS) I 50 patients of category 1 were included in this study and divided into two equal groups, 25 in each group. Group I received GA and group II received RSSA. Result - Time for anesthesia was more in the RSGA group than the RSSA group, which was statistically significant (P < 0.001). The time for surgical readiness was also significantly higher in the RSGA group in comparison to the RSSA group with P value of < 0.001, which was statistically significant but there was no significant difference in Incision to delivery time.